The functional analysis of sugar transporter proteins in sugar accumulation and pollen tube growth in pummelo (Citrus grandis) - Xu, Weiwei; Liu, Ziyan; Zhao, Zeqi; Zhang, Shuhang; Li, Mengdi; Guo, Dayong; Liu, Ji-Hong; Li, Chunlong (Frontiers in Plant Science, 2023)
Sugar transporter proteins (STPs) play vital roles in sugar transport and allocation of carbon sources in plants. However, the evolutionary dynamics of this important gene family and their functions are still largely unknown in citrus, which is the largest fruit crop in the world. In this study, fourteen non‑redundant CgSTP family members were identified in pummelo (Citrus grandis). A comprehensive analysis based on the biochemical characteristics, the chromosomal location, the exon–intron structures and the evolutionary relationships demonstrated the conservation and the divergence of CgSTPs. Moreover, CgSTP4, 11, 13, 14 were proofed to be localized in plasma membrane and have glucose transport activity in yeast. The hexose content were significantly increased with the transient overexpression of CgSTP11 and CgSTP14. In addition, antisense repression of CgSTP4 induced the shorter pollen tube length in vitro, implying the potential role of CgSTP4 in pummelo pollen tube growth. Taken together, this work explored a framework for understanding the physiological role of CgSTPs and laid a foundation for future functional studies of these members in citrus species.